(20a - 16a+b + 4b2) by 4a²b² divide
Answers
Answer:
STEP1:Equation at the end of step 1
((20•(a2))-10a) 1 ((———————————————•x)•x)•———————————————————— (a-1) ((16•(a3))-(24•5a2))
STEP 2 :
Equation at the end of step2:
((20•(a2))-10a) 1 ((———————————————•x)•x)•——————————————— (a-1) (24a3-(24•5a2))
STEP3:
1 Simplify ——————————— 16a3 - 80a2
STEP4:Pulling out like terms
4.1 Pull out like factors :
16a3 - 80a2 = 16a2 • (a - 5)
Equation at the end of step4:
((20•(a2))-10a) 1 ((———————————————•x)•x)•—————————— (a-1) 16a2•(a-5)
STEP 5 :
Equation at the end of step5:
((22•5a2)-10a) 1 ((——————————————•x)•x)•—————————— (a-1) 16a2•(a-5)
STEP6:
20a2 - 10a Simplify —————————— a - 1
STEP7:Pulling out like terms
7.1 Pull out like factors :
20a2 - 10a = 10a • (2a - 1)
Polynomial Long Division :
7.2 Polynomial Long Division
Dividing : 2a - 1
("Dividend")
By : a - 1 ("Divisor")
dividend 2a - 1 - divisor * 2a0 2a - 2 remainder 1
Quotient : 2
Remainder : 1
Equation at the end of step7:
10a•(2a-1) 1 ((——————————•x)•x)•—————————— a-1 16a2•(a-5)
STEP8:Equation at the end of step 8
10ax • (2a - 1) 1 (——————————————— • x) • —————————————— a - 1 16a2 • (a - 5)
STEP9:
Multiplying exponential expressions :
9.1 x1 multiplied by x1 = x(1 + 1) = x2
Equation at the end of step9:
10ax2 • (2a - 1) 1 ———————————————— • —————————————— a - 1 16a2 • (a - 5)
STEP10:
Dividing exponential expressions :
10.1 a1 divided by a2 = a(1 - 2) = a(-1) = 1/a1 = 1/a
Final result :
5x2 • (2a - 1) —————————————————————— 8a • (a - 1) • (a - 5)
Answer:
. y = -2b , z = -3c = (4a)2 + (–2b)2 + (–3c)2 + 2(4a)(–2b) + 2(–2b)(–3c) + 2(–3c)(4a) = 16a2 + 4b2 + 9c2 –